2021
DOI: 10.1002/solr.202100673
|View full text |Cite
|
Sign up to set email alerts
|

Frustrated Lewis Pairs Constructed on 2D Amorphous Carbon Nitride for High‐Selective Photocatalytic CO2 Reduction to CH4

Abstract: Photocatalytic reduction of CO2 into high value‐added fuels paves a new avenue for alleviating the energy crisis and green‐house effect, yet it is still challenging to achieve a highly active photocatalyst with high selectivity. Herein, for the first time, a facile structural engineering strategy is developed to construct tunable frustrated Lewis pairs (FLPs) on 2D amorphous graphitic carbon nitride (C3N4) via the introduction of boric acid with the assistance of supercritical CO2, wherein the FLPs are compose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…To fabricate the borate-functionalized 2D amorphous g-C 3 N 4 nanosheets (B-C 3 N 4 -X MPa), wherein B refers to the introduced boron bridges and X refers to the pressure of SC CO 2 , one-step SC CO 2 treatment was utilized, where H 3 BO 3 is used as the boron source. In this process, the straining and anisotropic acidic etching effect of SC CO 2 is expected to cleave the weak van der Waals forces between layers and the in-planar hydrogen bonds of tri-s-triazine units in the layers, thereby exfoliating bulk C 3 N 4 into 2D nanosheets, facilitating the formation of the amorphous and defective structure with -NH x groups [26][27][28][29][30] . Meanwhile, since H 3 BO 3 is presented over the preparation process, the empty sp 2 orbital on B of H 3 BO 3 is expected to be nucleophilic attacked by the lone pair of -NH x groups of the defected g-C 3 N 4 26 , forming in-planar bridging -B(OH)-groups (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To fabricate the borate-functionalized 2D amorphous g-C 3 N 4 nanosheets (B-C 3 N 4 -X MPa), wherein B refers to the introduced boron bridges and X refers to the pressure of SC CO 2 , one-step SC CO 2 treatment was utilized, where H 3 BO 3 is used as the boron source. In this process, the straining and anisotropic acidic etching effect of SC CO 2 is expected to cleave the weak van der Waals forces between layers and the in-planar hydrogen bonds of tri-s-triazine units in the layers, thereby exfoliating bulk C 3 N 4 into 2D nanosheets, facilitating the formation of the amorphous and defective structure with -NH x groups [26][27][28][29][30] . Meanwhile, since H 3 BO 3 is presented over the preparation process, the empty sp 2 orbital on B of H 3 BO 3 is expected to be nucleophilic attacked by the lone pair of -NH x groups of the defected g-C 3 N 4 26 , forming in-planar bridging -B(OH)-groups (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1a, b). Specifically, the introduction of planar B into the g-C 3 N 4 motif is accomplished by supercritical CO 2 treatment, which has been well demonstrated in heteroatom doping [24][25][26] . To our knowledge, introducing bridging B to establish the exchange of local magnetic moments and form long-range magnetic order, tuning magnetic property of 2D materials is proposed for the first time.…”
mentioning
confidence: 99%
“…Considering the phase transition in crystal structure relying on pressure and temperature, strain engineering of SC CO 2 plays a key role in the morphology evolution, lattice distortion, and destruction of 2D materials. [ 151–159 ] Through altering the pressure and temperature, single‐layer 2D VS 2 nanosheets have been successfully obtained in SC CO 2 expanded solvent systems (such as water/SC CO 2 /NMP). [ 160 ] The experiment results showed that the similar surface energies of NMP and VS 2 , the enhanced solubility and diffusivity of VS 2 , and anisotropic etching are critical factors in the exfoliation efficiency.…”
Section: Sc Co2‐assisted Fabrication Of 2d Materialsmentioning
confidence: 99%
“…Considering the phase transition in crystal structure relying on pressure and temperature, strain engineering of SC CO 2 plays a key role in the morphology evolution, lattice distortion, and destruction of 2D materials. [151][152][153][154][155][156][157][158][159] Through altering [143] Copyright 2021, Wiley-VCH.…”
Section: Sc Co 2 -Induced Strain Engineeringmentioning
confidence: 99%
“…29 Particularly, selective production of CH 4 from CO 2 photoreduction was witnessed by constructing an amorphous phase on crystalline photocatalysts such as titania (TiO 2 ) and graphitic carbon nitride (g-C 3 N 4 ). 30,31 Therefore, the construction of a crystalline-amorphous homojunction in semiconductor photocatalysts is a promising approach to boost the photoactivity and selectivity of CO 2 reduction. Nonetheless, the fabrication of a crystalline-amorphous interface in photocatalysts usually involves complex synthesis procedures, such as acid treatment on the catalyst surface or thermal treatment under H 2 -rich conditions at high temperature.…”
Section: Introductionmentioning
confidence: 99%